2023
DOI: 10.3389/fmicb.2022.1090197
|View full text |Cite
|
Sign up to set email alerts
|

Genomic study and lipidomic bioassay of Leeuwenhoekiella parthenopeia: A novel rare biosphere marine bacterium that inhibits tumor cell viability

Abstract: The fraction of low-abundance microbiota in the marine environment is a promising target for discovering new bioactive molecules with pharmaceutical applications. Phenomena in the ocean such as diel vertical migration (DVM) and seasonal dynamic events influence the pattern of diversity of marine bacteria, conditioning the probability of isolation of uncultured bacteria. In this study, we report a new marine bacterium belonging to the rare biosphere, Leeuwenhoekiella parthenopeia sp. nov. Mr9T, which was isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 120 publications
1
3
0
Order By: Relevance
“…Besides, the exploration of secondary/specialized metabolism combined with phylogenomic and evolutionary studies is shown to be a valuable strategy to assess the biosynthetic potential of new microbial groups, either at the species level or in an overall context. Finally, this and other recent studies (Ramírez-Durán et al, 2021 ; Gattoni et al, 2023 ) show that rare and minority bacteria harbor untapped metabolic potential for synthesizing novel, biotechnologically significant compounds. A good example is the new marine bacterium R. domitiana V10 T , which is theoretically able to produce plant-promoting compounds and antitumor molecules, which merits prioritizing future in vitro studies.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Besides, the exploration of secondary/specialized metabolism combined with phylogenomic and evolutionary studies is shown to be a valuable strategy to assess the biosynthetic potential of new microbial groups, either at the species level or in an overall context. Finally, this and other recent studies (Ramírez-Durán et al, 2021 ; Gattoni et al, 2023 ) show that rare and minority bacteria harbor untapped metabolic potential for synthesizing novel, biotechnologically significant compounds. A good example is the new marine bacterium R. domitiana V10 T , which is theoretically able to produce plant-promoting compounds and antitumor molecules, which merits prioritizing future in vitro studies.…”
Section: Discussionsupporting
confidence: 62%
“…nov. Given that this strain was isolated from winter nocturnal samples of the coastal surface, while R. ekhonensis was cultured from the depths of a hypersaline lake, the isolation of strain V10 T supports the use of night-time and seasonal sampling as a strategy for the cultivation of new microorganisms, an approach that we successfully used in a previous study and allowed the isolation of Leeuwenhoekiella parthenopeia , a new rare biosphere bacterium that inhibits the proliferation of tumor cells (Gattoni et al, 2023 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In terms of microbial diversity, the oceans represent the largest biosphere habitat, containing about 70% of the prokaryotic biomass [1]. In recent decades, interest in the bioactive compounds from marine bacteria has grown enormously [2][3][4][5][6][7][8], and many works have focused on rare marine Actinomycetota [9][10][11][12][13]. One of the most intriguing and rare genera of marine Actinomycetota is Euzebya.…”
Section: Introductionmentioning
confidence: 99%